2015
DOI: 10.1111/bph.12958
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder inflammation induces changes in urothelial nerve growth factor andTRPV1 channels

Abstract: During bladder inflammation, increased production of NGF in urothelial cells induced increased expression and activity of TRPV1 channels in the cell membrane. This effect was primarily mediated by the PI3K pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
2
32
0
2
Order By: Relevance
“…Under inflammatory conditions, a TrKA blocker was able to inhibit pain behavior. Furthermore, bladder inflammation increased expression of TRPV1 channels in the membrane of urothelial cells . Mechanical bladder hyperactivity, typical of cystitis, was antagonized by a TRPV1 blocker and was not revealed in TRPV1 KO mice .…”
Section: Pathophysiological Rolesmentioning
confidence: 95%
“…Under inflammatory conditions, a TrKA blocker was able to inhibit pain behavior. Furthermore, bladder inflammation increased expression of TRPV1 channels in the membrane of urothelial cells . Mechanical bladder hyperactivity, typical of cystitis, was antagonized by a TRPV1 blocker and was not revealed in TRPV1 KO mice .…”
Section: Pathophysiological Rolesmentioning
confidence: 95%
“…For instance, colonic NGF and TrkA expression were increased in inflammatory bowel disease (IBD) patients (di Mola et al, 2000), and the NGF level in ulcerative colitis was positively correlated with the severity of the disease . In rat models of chemically-induced cystitis, rats exhibited inflammatory bladder pain, skin mechanical hypersensitivity, and increased NGF content in the bladder mucosa; administration of TrkA antagonist before modeling prevented bladder and skin hyperalgesia, suggesting that coupled with TrkA, NGF transmits signals to the sensory neurons, activates pain pathway, and mediates hypersensitivity (Coelho et al, 2015).…”
Section: Mechanisms Of Ngf-mediated Vhmentioning
confidence: 99%
“…A study using TRPV1 knockout mice showed that TRPV1 regulated bladder function and mechanically evoked signaling . IL‐1β and NGF promoted the expression of TRPV1 . The bladders of patients with OAB showed chronic inflammation and increased expression of TRPV1 .…”
Section: Discussionmentioning
confidence: 99%